82: Educational Program On Developmentally-Supportive Care for Parents of Extremely Preterm Children: A Pilot Study. Issue 6 (1st June 2014) - Yung, A; Xie, L; Côté, S; Karsenti, T; Gosselin, J; Walker, D; Luu, T
Abstract: BACKGROUND: Developmental interventions for parents of preterm infants have been shown to improve parental outcomes. We developed a family-focused educational program of developmentally-supportive care using a multimodal approach that integrates web-based technologies. OBJECTIVES: To assess the effect of our program on parental outcomes at four months corrected age (CA) among parents of extremely preterm infants. DESIGN/METHODS: Preliminary clinical trial with a historical comparison group. Families with preterm infants born <29 weeks and admitted at Ste-Justine Hospital NICU were recruited, with a total of 55 in each comparison and intervention groups. At four months CA, parents completed the Parental Cognitions and Conduct Toward the Infant scale, the Parenting Stress Index, and the Bates Parental Perception of Infant Temperament scale. Comparisons were made using T-test and chi square analyses. RESULTS: Mean gestational age was 27±3 weeks and birth weight 1010±236 g. The table shows parental outcomes by intervention group (table1). Analyses with the current available data (comparison: n=48, intervention: n=38), demonstrated no significant difference between the two groups regarding mean scores and proportion of parents scoring in the abnormal range. CONCLUSIONS: The program in the present format did not show benefits on short-term parental outcomes. Using a more interactive and individualized web-based approach may be an option for improving our program and outcomes.